Insulin-regulated aminopeptidase contributes to setting the intensity of FcR-mediated inflammation - Bratti, Manuela; Vibhushan, Shamila; Longé, Cyril; Koumantou, Despoina; Ménasché, Gaël; Benhamou, Marc; Varin-Blank, Nadine; Blank, Ulrich; Saveanu, Loredana; Ben Mkaddem, Sanae (Frontiers in Immunology, 2022)
The function of intracellular trafficking in immune-complex triggered inflammation remains poorly understood. Here, we investigated the role of Insulin-Regulated Amino Peptidase (IRAP)-positive endosomal compartments in Fc receptor (FcR)-induced inflammation. Less severe FcR-triggered arthritis, active systemic anaphylaxis and FcRI-triggered passive systemic anaphylaxis were observed in IRAP-deficient versus wild-type mice. In mast cells FcRI stimulation induced rapid plasma membrane recruitment of IRAP-positive endosomes. IRAP-deficient cells exhibited reduced secretory responses, calcium signaling and activating SykY519/520 phosphorylation albeit receptor tyrosine phosphorylation on  and  subunits was not different. By contrast, in the absence of IRAP, SHP1-inactivating phosphorylation on Ser591 that controls Syk activity was decreased. Ex-vivo cell profiling after FcR-triggered anaphylaxis confirmed decreased phosphorylation of both SykY519/520 and SHP-1S591 in IRAP-deficient neutrophils and monocytes. Thus, IRAP-positive endosomal compartments, in promoting inhibition of SHP-1 during FcR signaling, control the extent of phosphorylation events at the plasma membrane and contribute to setting the intensity of immune-complex triggered inflammatory diseases.